Augmented reality game related injuries. (November 2017) - Richards, Kate; Wong, Kai; Khan, Mansoor
Abstract : Introduction: There are an increasing number of reported injuries associated with ambulatory mobile phone use. PokemonGo is one of the first mobile augmented reality games. We present a case of electrical burns in a PokemonGo player. Case description: A young male sustained high voltage electrical burns from falling onto a railway track whilst playing PokemonGo. Injuries involved 7% full thickness burns affecting both lower limbs, chest, right elbow and right maxilla. This was associated with loss of motor function in his right foot. Emergency fasciotomies were performed. He required extensive wound debridement, including a large portion of his extensor mechanism. Rhabdomyolysis was treated with intravenous fluids. Due to extensive loss of anterior thigh muscles and common peroneal nerve damage from the injury, he subsequently had an above knee amputation. Results and Conclusions: Mobile phone use by drivers is widely acknowledged to contribute towards accidents and injuries. Pedestrian mobile use has been identified as having a similar effect on user safety. The rate of increase of pedestrian injuries associated with mobile phone use surpasses that of motor vehicle drivers, although it is anticipated that this remains under-reported. Mobile phone use impacts on situational awareness and causes temporary user distraction. In addition augmented reality games blur the distinction between the physical and computer world, impairing judgement. Recently safety measures targeting distracted pedestrians have been considered. These include education, signs, separated walkways for device users and fines. Take home message: Use of mobile devices impairs situational awareness and co-ordination. Increased awareness and reporting of injuries associated with device use is important in informing the public and healthcare providers. Further measures are required to target this public safety concern.